2006
DOI: 10.1186/1465-9921-7-73
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor signaling in the pathophysiology of asthma and COPD

Abstract: Anticholinergics are widely used for the treatment of COPD, and to a lesser extent for asthma. Primarily used as bronchodilators, they reverse the action of vagally derived acetylcholine on airway smooth muscle contraction. Recent novel studies suggest that the effects of anticholinergics likely extend far beyond inducing bronchodilation, as the novel anticholinergic drug tiotropium bromide can effectively inhibit accelerated decline of lung function in COPD patients. Vagal tone is increased in airway inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
334
0
12

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(357 citation statements)
references
References 144 publications
(153 reference statements)
11
334
0
12
Order By: Relevance
“…These results are in full coherence with the results of the author Mue Mue et al [25]. In addition to the bronchodilator effect, author Gosens et al suggest that anticholinergic substances, especially those of extended action like tiotropium bromide, might also reduce the constriction of lung functions [26].…”
Section: Discussionsupporting
confidence: 80%
“…These results are in full coherence with the results of the author Mue Mue et al [25]. In addition to the bronchodilator effect, author Gosens et al suggest that anticholinergic substances, especially those of extended action like tiotropium bromide, might also reduce the constriction of lung functions [26].…”
Section: Discussionsupporting
confidence: 80%
“…21) Recent reports have suggested that tiotropium bromide has anti-inflammatory activity via the muscarinic M3 receptor. 22) In this study, WBC counts and CRP levels were relatively lower after than before treatment, but there were no significant differences because their values were within normal ranges even before treatment. These results suggest that tiotropium inhibits systemic inflammatory reactions, which might lead to beneficial effects on LV diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, this muscarinic activation seems to be involved in the remodelling and functional changes of ASM described in asthma and COPD as described in references [1][2][3][4][5][6]73]. We discussed the existence of two cGMP signals, at 20-s and 60-s in [36], which are products of two distinctive guanylyl cyclases, the NO-sensitive soluble guanylyl cyclases (NO-sGC) and Natriuretic Peptide Receptor Guanylyl Cyclase-B (NPR-GC-B).…”
Section: Resultsmentioning
confidence: 99%
“…Statistically significant difference between the Control with respect to mastoparan as indicated with asterisk (*p<0.05). Thus, a dysfunction of these M2/M3AChR signal transducing cascades has been implied in the pathophysiological mechanisms of bronchial asthma as mentioned in references [1,3,4] and Chronic Obstructive Pulmonary Disease (COPD) in [3]. In this sense, we attempted to evaluate these novel signal transducing cascades involving guanylyl cyclase activities above discussed, in an experimental asthma model in rats as described in reference [70].…”
Section: Body: Cyclic Gmp Signals During Muscarinic Activationmentioning
confidence: 99%
See 1 more Smart Citation